PERAN PENDIDIKAN PESANTREN DALAM MEMBENTUK PEMAHAMAN SANTRIWATI TENTANG HAID DAN ISTIHADHAH DI PONDOK PESANTREN DARUSSALAM PARMERAAN PADANG LAWAS UTARA - Rani Syahfitri Ritonga; Mesran Mesran; Irwansyah Irwansyah (Fakultas Agama Islam Universitas Al Washliyah, 2025)
This study aims to explore the level of understanding among female students (santriwati) regarding menstruation (haid) and abnormal bleeding (istihadhah), and to analyze the role of Islamic boarding school (pesantren) education in providing such knowledge. The research was conducted at Pondok Pesantren Darussalam Parmeraan in early May 2025 using a qualitative descriptive approach. Data were collected through in-depth interviews with the school principal, religious teachers, and the female students. The findings indicate that the students’ theoretical understanding is relatively good, although challenges remain in differentiating between haid and istihadhah in complex cases. The pesantren plays an active role through fiqh lessons, classical Islamic texts (kitab kuning), and open discussions. Supporting factors include relevant teaching methods and teacher openness, while inhibiting factors include lack of visual aids and students’ reluctance to ask questions due to shyness. The study recommends enhancing teaching methods and applying more interactive approaches to improve comprehension.